Case Report: Delayed diagnosis of parathyroid carcinoma and two pulmonary recurrences and metastases - Tian, Wenzhi; Hu, Chenchen; Cao, Tianmin; Chen, Dong; Su, Xi; Li, Peng (Frontiers in Oncology, 2025)
Parathyroid carcinoma (PC) is a rare and aggressive malignancy, characterized by severe hypercalcemia and elevated parathyroid hormone (PTH) levels, making it particularly challenging to diagnose. In this case report, the patient’s PC was not diagnosed during the initial surgery. The diagnosis was delayed until two years later, when metastatic lesions appeared in the lungs, leading to repeat surgery and a retrospective review of the patient’s medical history. This case emphasizes the diagnostic difficulty of PC, particularly during the initial evaluation. Close postoperative follow-up is crucial for suspected cases. Upon biochemical evidence of recurrence, comprehensive systemic screening should be conducted, not only focusing on the neck but also on common metastatic sites such as the lungs, bones, and liver.